Wpływ klasyfikacji podmiotów gospodarczych na efektywność modelowania podstawowych kategorii ekonomicznych małych przedsiębiorstw - Dehnel, Grażyna (Effect of Small Business Classification on the Estimation Precision of Basic Economic Information, 2007)
According to Central Statistical Office there were about 1,6 million small (called small business) in Poland in 2001 - over 95% of all enterprises. Although the small economic entities constitute the basis of local economy there is no information about this group of enterprises available at regional and local level. One of the major problems involved in estimating information about economic activity across domains is the distribution of small companies variables. The study variable may be highly skewed, there may be a large proportion of zero responses and there may be several auxiliary variables that can be used to improve estimation but these may include some extreme values. This article presents Chamber's Model which examines the behaviour of GREG estimators taking into account data classification. It shows how an efficient Chambers Model was found for a business survey.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 472-481